Efficiency of the Simplex Method

Exercise 4.1

Table 8 Pivots

Largest-Coefficient Rule

Smallest-Index Rule

\(x_2 \leftrightarrow w_3\)

\(x_1 \leftrightarrow w_2\)

\(x_1 \leftrightarrow w_1\)

\(x_2 \leftrightarrow w_1\)

\(w_2 \leftrightarrow w_3\)

Exercise 4.2

Table 9 Pivots

Largest-Coefficient Rule

Smallest-Index Rule

\(x_1 \leftrightarrow w_1\)

\(x_1 \leftrightarrow w_1\)

\(x_2 \leftrightarrow x_1\)

\(x_2 \leftrightarrow x_1\)

Exercise 4.3

Table 10 Pivots

Largest-Coefficient Rule

Smallest-Index Rule

\(x_2 \leftrightarrow w_3\)

\(x_1 \leftrightarrow w_2\)

\(x_1 \leftrightarrow w_1\)

\(x_2 \leftrightarrow w_1\)

\(w_3 \leftrightarrow w_2\)

Exercise 4.4

\[\begin{split}\begin{aligned} \text{maximize} \quad \zeta &= 100 x_1 + 10 x_2 + x_3\\ \text{subject to} \quad w_1 &= 1 - x_1\\ w_2 &= 100 - 20 x_1 - x_2\\ w_3 &= 10000 - 200 x_1 - 20 x_2 - x_3\\ x_i &\geq 0 \quad i = 1, 2, 3\\ w_i &\geq 0 \quad i = 1, 2, 3 \end{aligned}\end{split}\]

Initial feasible solution:

\[x_1 = 0, \quad x_2 = 0, \quad x_3 = 0, \quad w_1 = 1, \quad w_2 = 100, \quad w_3 = 10000.\]

Choose \(x_3\) and \(w_3\) as the entering and leaving variable respectively where

\[x_3 = \min\left\{ w_3 \right\}_{\geq 0} = \min\left\{ 10000 \right\}_{\geq 0}.\]

Update the current dictionary’s feasible solution to

\[x_1 = 0, \quad x_2 = 0, \quad x_3 = 10000, \quad w_1 = 1, \quad w_2 = 100, \quad w_3 = 0.\]

Pivot dictionary to

\[\begin{split}\begin{aligned} \text{maximize} \quad \zeta &= 10000 - 100 x_1 - 10 x_2 - w_3\\ \text{subject to} \quad w_1 &= 1 - x_1\\ w_2 &= 100 - 20 x_1 - x_2\\ x_3 &= 10000 - 200 x_1 - 20 x_2 - w_3\\ x_i &\geq 0 \quad i = 1, 2, 3\\ w_i &\geq 0 \quad i = 1, 2, 3 \end{aligned}\end{split}\]

Exercise 4.5

\[\begin{split}\begin{aligned} \text{maximize} \quad \zeta &= -4 b_1 - 2 b_2 - b_3 + 8 x_1 + 4 x_2 + 2 x_3 + x_4\\ \text{subject to} \quad w_1 &= b_1 - x_1\\ w_2 &= 2 b_1 + b_2 - 4 x_1 - x_2\\ w_3 &= 4 b_1 + 2 b_2 + b_3 - 8 x_1 - 4 x_2 - x_3\\ w_4 &= 8 b_1 + 4 b_2 + 2 b_3 + b_4 - 16 x_1 - 8 x_2 - 4 x_3 - x_4\\ x_i &\geq 0 \quad i = 1, 2, 3, 4\\ w_i &\geq 0 \quad i = 1, 2, 3, 4 \end{aligned}\end{split}\]
\[\begin{split}x_1 &\leftrightarrow w_1\\ x_2 &\leftrightarrow w_2\\ w_1 &\leftrightarrow x_1\\ x_3 &\leftrightarrow w_3\\ x_1 &\leftrightarrow w_1\\ w_2 &\leftrightarrow x_2\\ w_1 &\leftrightarrow x_1\\ x_4 &\leftrightarrow w_4\\ x_1 &\leftrightarrow w_1\\ x_2 &\leftrightarrow w_2\\ w_1 &\leftrightarrow x_1\\ w_3 &\leftrightarrow x_3\\ x_1 &\leftrightarrow w_1\\ w_2 &\leftrightarrow x_2\\ w_1 &\leftrightarrow x_1\\\end{split}\]

Exercise 4.6

Since \(w_{i < k}\) do not contain \(x_k\), pivoting \(x_k \leftrightarrow w_k\) will only affect \(x_k\), \(w_k\), \(\zeta\), and \(w_{k < i \leq n}\):

\[\begin{split}x_k &= \sum_{j = 1}^{k - 1} \epsilon_k \epsilon_j 10^{k - j} (b_j - 2 x_j) + (b_k - w_k) = \sum_{j = 1}^{k - 1} \epsilon'_k \epsilon'_j 10^{k - j} (b_j - 2 x_j) + (b_k - w_k)\\ \\ w_{i < k} &= \sum_{j = 1}^{i - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) + (b_k - x_i) = \sum_{j = 1}^{i - 1} \epsilon'_i \epsilon'_j 10^{i - j} (b_j - 2 x_j) + (b_k - x_i)\end{split}\]
\[\begin{split}\zeta &= -\sum_{j = 1}^n \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right)\\ &= -\epsilon_k 10^{n - k} \left( \frac{1}{2} b_k - x_k \right) - \sum_{j = 1}^{k - 1} \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right) - \sum_{j = k + 1}^n \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right)\\ &= -\epsilon_k 10^{n - k} \frac{1}{2} b_k + \epsilon_k 10^{n - k} \left[ \sum_{j = 1}^{k - 1} \epsilon_k \epsilon_j 10^{k - j} (b_j - 2 x_j) + (b_k - w_k) \right] - \sum_{j = 1}^{k - 1} \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right) - \sum_{j = k + 1}^n \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right)\\ &= -\epsilon_k 10^{n - k} \frac{1}{2} b_k + \epsilon_k 10^{n - k} (b_k - w_k) + \sum_{j = 1}^{k - 1} \epsilon_j 10^{n - j} (b_j - 2 x_j) - \sum_{j = 1}^{k - 1} \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right) - \sum_{j = k + 1}^n \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right) & \quad & \text{since}\ \epsilon_k^2 = 1\\ &= \left[ \sum_{j = 1}^{k - 1} \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right) \right] + \epsilon_k 10^{n - k} \left( \frac{1}{2} b_k - w_k \right) - \sum_{j = k + 1}^n \epsilon_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right)\\ &= -\epsilon'_k 10^{n - k} \left( \frac{1}{2} b_k - w_k \right) - \sum_{j = 1, j \neq k}^n \epsilon'_j 10^{n - j} \left( \frac{1}{2} b_j - x_j \right)\end{split}\]
\[\begin{split}w_{i > k} &= \sum_{j = 1}^{i - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) + (b_k - x_i)\\ &= (b_k - x_i) + \epsilon_i \epsilon_k 10^{i - k} (b_k - 2 x_k) + \sum_{j = 1}^{k - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) + \sum_{j = k + 1}^{i - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j)\\ &= (b_k - x_i) + \epsilon_i \epsilon_k 10^{i - k} b_k - 2 \epsilon_i \epsilon_k 10^{i - k} \left[ (b_k - w_k) + \sum_{j = 1}^{k - 1} \epsilon_k \epsilon_j 10^{k - j} (b_j - 2 x_j) \right] + \sum_{j = 1}^{k - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) + \sum_{j = k + 1}^{i - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j)\\ &= (b_k - x_i) - \epsilon_i \epsilon_k 10^{i - k} (b_k - 2 w_k) - 2 \sum_{j = 1}^{k - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) + \sum_{j = 1}^{k - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) + \sum_{j = k + 1}^{i - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) & \quad & \text{since}\ \epsilon_k^2 = 1\\ &= \left[ -\sum_{j = 1}^{k - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) \right] - \epsilon_i \epsilon_k 10^{i - k} (b_k - 2 w_k) + \left[ \sum_{j = k + 1}^{i - 1} \epsilon_i \epsilon_j 10^{i - j} (b_j - 2 x_j) \right] + (b_k - x_i)\\ &= \epsilon'_i \epsilon'_k 10^{i - k} (b_k - 2 w_k) + \sum_{j = 1, j \neq k}^{i - 1} \epsilon'_i \epsilon'_j 10^{i - j} (b_j - 2 x_j) + (b_k - x_i)\end{split}\]

where \(\epsilon'_{i < k} = -\epsilon_{i < k}\), \(\epsilon'_k = -\epsilon_k\), and \(\epsilon'_{i > k} = \epsilon_{i > k}\).

Exercise 4.7

Let \(\epsilon_i^t\) denote the relationship between the \(\epsilon_i\)’s before and after each pivot. Evidently, \(\epsilon_i^{t = 0} = 1\) for all \(1 \leq i \leq n\).

As shown in Exercise 4.6, pivoting between \(x_k\) and \(w_k\) results in a dictionary that is of the same form as before. The only significant differences are the sign changes of \(\epsilon_i\)’s:

\[\begin{split}\epsilon_i^{t + 1} = \begin{cases} -\epsilon_i^t & \text{if}\ i \leq k\\ \epsilon_i^t & \text{otherwise.} \end{cases}\end{split}\]

Observe that applying the simplex method’s largest-coefficient rule in this case is equivalent to picking the first positive \(\epsilon_k^t\) where \(k\) is the smallest subscript over the ordered sequence \(\left[ \epsilon_1^t, \epsilon_2^t, \ldots, \epsilon_n^t \right]\).

Let \(T(n)\) denote the number of iterations (i.e. pivots) needed before selecting the variable associated with \(\epsilon_{n + 1}\) as the entering variable for the first time.

From the initial conditions, obviously \(T(0) = 1\). Now that \(\epsilon_1^{t = 1}\) is negative, \(\epsilon_2^{t = 1}\) is chosen as the next entering variable. Pivoting will make \(\epsilon_1^{t = 2}\) eligible as an entering variable again, which means the same sequence of pivots \(T(0)\) needs to occur before \(\epsilon_3\) can even be considered as the next entering variable. Thus, \(T(1) = 1 + T(0) = 2\). This process generalizes to the following geometric series

\[T(n) = 1 + \sum_{i = 0}^{n - 1} T(i) = 1 + 2 + 4 + 8 + \cdots = a \frac{1 - r^n}{1 - r}\]

where \(a = 1\) and \(r = 2\). Therefore, the Klee-Minty problem requires \(2^n - 1\) iterations.

Exercise 4.8

Rewriting the Klee-Minty problem with \(b_i = \beta^{i - 1}\) where \(\beta > 1\) yields

\[\sum_{j = 1}^{i - 1} 10^{i - j} b_j + b_i = \sum_{j = 1}^{i - 1} 10^{i - j} \beta^{j - 1} + \beta^{i - 1}\]

and

\[\begin{split}\begin{array}{*{5}{@{}c@{}}} 0 & \leq & x_1 & \leq & 1\\ 0 & \leq & x_2 & \leq & 10 + \beta\\ 0 & \leq & x_3 & \leq & 10^2 + 10 \beta + \beta^2\\ 0 & \leq & x_4 & \leq & 10^3 + 10^2 \beta + 10 \beta^2 + \beta^3\\ & & \vdots & &\\ 0 & \leq & x_n & \leq & \sum_{j = 1}^{n - 1} 10^{n - j} \beta^{j - 1} + \beta^{n - 1}. \end{array}\end{split}\]

In order to force the simplex method to proceed as in Exercise 4.7, \(\beta\) needs to be chosen such that the leaving variable’s subscript matches the entering variable’s subscript.

Suppose the entering variable’s index is \(e \in \mathcal{N}\) and let \(l \in \mathcal{B}\) denote the leaving variable’s index. From the definition of the Klee-Minty problem, \(l \geq e\). Out of the remaining possible candidates, the minimum ratio test chooses one according to:

\[\frac{\hat{b}_l}{\hat{a}_{le}} = \min\left\{ \frac{\hat{b}_i}{\hat{a}_{ie}} \colon i \in \mathcal{B}, \hat{b}_i \in \left[ \beta^{i - 1} - \sum_{j = 1}^{i - 1} 10^{i - j} \beta^{j - 1}, \beta^{i - 1} + \sum_{j = 1}^{i - 1} 10^{i - j} \beta^{j - 1} \right]_{\geq 0}, \hat{a}_{ie} = \epsilon'_i \epsilon'_e \cdot 2^{1 - \delta_{i - e}} \cdot 10^{i - e} > 0 \right\}.\]

Observe that for \(l = k > e\) to be even feasible where \(k\) represents another leaving variable, the intervals represented by \(\frac{\hat{b}_e}{\hat{a}_{ee}}\) and \(\frac{\hat{b}_k}{\hat{a}_{ke}}\) need to intersect. Since each constraint’s upper bound (i.e. the right hand side of each inequality) grows exponentially in terms of \(\beta\) and each pivot only induces sign changes, if the pair of intervals indexed by \(e = 1\) and \(l = n \neq e\) never overlaps, no pair of intervals in between them will intersect. Therefore, the infimum (a.k.a. greatest lower bound) satisfies

\[\begin{split}\frac{\hat{b}_e}{\hat{a}_{ee}} &< \frac{\hat{b}_l}{\hat{a}_{le}}\\ 1 &< \frac{ \beta^{n - 1} - \sum_{j = 1}^{n - 1} 10^{n - j} \beta^{j - 1} }{ 2^{1 - \delta_{n - 1}} \cdot 10^{n - 1} }\\ 2 \cdot 10^{n - 1} &< \beta^{n - 1} - \sum_{j = 1}^{n - 1} 10^{n - j} \beta^{j - 1}.\end{split}\]

Exercise 4.9

Recall that Stirling’s approximation is

\[n! \approx \left( \frac{n}{e} \right)^n \sqrt{2 \pi n}.\]

A crude estimate for the desired binomial coefficient is then

\[{2n \choose n} = \frac{(2n)!}{n! (2n - n)!} \approx \frac{2^{2n} (n / e)^{2n} \cdot 2 \sqrt{\pi n}}{(n / e)^{2n} \cdot 2 \pi n} = \frac{2^{2n}}{\sqrt{\pi n}}.\]

From inspection,

\[\frac{2^{2n}}{2n} \leq \frac{2^{2n}}{2 \sqrt{n}} \leq {2n \choose n} \leq 2^{2n}\]

holds for any positive integer \(n\).

Exercise 4.10

Recall that a feasible solution satisfies all of the constraints. If that is no longer a requirement, Exercise 2.15 has illustrated the desired dictionary can be arrived at in exactly \(k\) pivots via the following process.

  1. Pivot all the non-zero elements that have the matching indices first i.e. \(x_i \leftrightarrow w_i\).

  2. The remaining pivots are degenerate and require adopting the convention of treating \(\frac{0}{0} = 0\).